THE IMPLEMENTATION OF STATE DEFENSE EDUCATION FOR THE HEADS OF LOCAL GOVERNMENT AS AN EFFORT TO PREVENT CORRUPTION - G. Theodorus L. Toruan (Asia Pacific Fraud Journal, 2018)
Corruption is an extraordinary crime that has become a major problem in Indonesia. Most of the perpetrators of corruption are the heads of local governments. In general, they commit corruption because they have authority and power. Based on the Corruption Perception Index 2016, Indonesia is ranked 4th in ASEAN. This index shows that corruption is still one of the state biggest problems in Indonesia. This paper uses descriptive qualitative method and the data collection is conducted using library research. The recommendation put forward through this paper is that the Heads of Local Government in Indonesia should join State Defense Education and Training. In addition, the Heads of Local Government should be able to become the role models for the people.